Examining rhetorical strategies in humorous discourses: a systematic review - Tianli, Zhou; Mansor, Nor Shahila; Ang, Lay Hoon; Sharmini, Sharon (Sciedu Press, 2022)
The purpose of this systematic review is to review the relevant studies on rhetorical strategies in humorous discourse and text to gain a comprehensive understanding of the role of rhetorical strategies in humorous discourse and to explore future research trends. A systematic literature review following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses was conducted in the present study. After data selection and screening followed the protocol criteria, 20 articles were included in this study. The results reveal that most of the prior researchers investigated one specific rhetorical strategy in an article, such as irony, metaphor, satire, insults, and metonymy, while some of them examined different rhetorical strategies simultaneously. Besides, all the included articles adopted a qualitative research method, and the theories they applied are diverse. Moreover, the functions of rhetorical strategies in different humorous discourses are summarized. The results show that the functions of rhetorical strategies differ in different types of humorous contexts, which depend on the speaker’s communication purpose in certain situations.